Prediction of WBGT for the Tokyo 2020 Olympic Marathon - Kashimura, O.; Minami, K.; Hoshi, A. (Japanese Journal of Biometeorology, 2016)
The heat during the Tokyo 2020 Summer Olympics will presumably be especially demanding for marathon runners. Therefore, the present study measured WBGT over the same three days in 2015 which correspond with the event in 2020. By using a road bike with mounted environmental thermometers, a run-through of the scheduled course from start to finish at a speed of 20 km/hr was simulated. Simulation conditions which included the speed of the marathon runners along with WBGT exposure that they could expect were examined to assess the related risk of heat stroke. The mean WBGT over the entire course on the road-bike was 30.4°C and thus higher than 30°C on July 26, and 29.6°C on August 4 and 26.9°C on August 9. The mean dry-bulb temperatures were 36.9°C on July 26, 34.5°C on August 4, and 32.4°C on August 9. The mean WBGT values obtained from concurrent stationary measurements at five locations along the course were just 0.2±0.1°C (range 0.1 to 0.3°C) higher than the mean values obtained from the moving road-bike measurements. These WBGT values indicate that athletes are exposed to a higher temperature while running than that commonly expected, which, along with the additional burden of body-temperature elevation occurring during an over 2-hour long marathon, sufficient training and acclimation under summer heat will be necessary to avoid heat stroke and permit a high level of performance. In this study, we set start time for marathon at 8:30, but think the start time to have to shift early in the morning. Furthermore, we install much mist showers in the marathon course route and think that it is necessary to make use for the physical cooling of the marathon runner.